Faktor-Faktor yang Mempengaruhi Komplikasi pada Kehamilan di Puskesmas Perawatan Terangun Nangroe Aceh Darussalam Tahun 2024 - Erna Wati; Ester Simanullang; Febriana Sari (STIKes Ibnu Sina Ajibarang, 2025)
Unhealthy pregnancies will affect the health of the mother and baby, which can lead to fatal pregnancies and even obstructed labor and breastfeeding. So in pregnancy, care is needed during pregnancy which needs to be monitored by carrying out routine ANC so that early examination or detection can be carried out since pregnancy. The aim of the research is to find out in depth what factors influence complications in pregnancy at the Terangun Nursing Health Center in 2024. This research uses a descriptive design with a quantitative type of research using case control research and a retrospective approach where the research takes data from the past. . The research sample was pregnant women who experienced complications and who did not experience pregnancy complications. Research results Age influences the occurrence of complications in trimester pregnancies with the results of the chi-square statistical test on maternal age, namely ρ=0.006<0.05. Parity influences the occurrence of complications in the third trimester of pregnancy with the results of the chi-square test, namely ρ=0.020<0.05. Pregnancy spacing influences the occurrence of complications in the third trimester of pregnancy using the chi-square test, namely ρ=0.018<0.05. Research suggestions: It is hoped that health workers, especially midwives in hospitals, will be able to provide counseling and education regarding the danger signs of complications that may occur in the third trimester of pregnancy..